Biomimetic design. Heteronomy and autopoiesis in the integration between technology and biology - Caldera, Carlo; Manni, Valentino; Valzano, Luca Saverio (TECHNE - Journal of Technology for Architecture and Environment, 2021)
Applying systemic thinking to the resolution of complexity in biomimetic design allows technological integration between biological and man-made systems, thereby creating an autopoietic building organism. Emulating Nature in projects requires know-how cross-fertilization and hybridization. Mechanical solutions and those associated with the properties of materials are by no means the only options adaptive architecture can resort to in reproducing natural processes. This paper illustrates experiences that adopt adaptive autopoietic strategies at both urban and architectural product level. These strategies are typical of the natural world and involve the integration of technology and biology. The described experiences aim at highlighting the link between biomimetic design and the heteronomy of disciplines.